Evaluation of the marsh deer stifle joint by imaging studies and gross anatomy - Shigue, D. A. [UNESP]; Rahal, S. C. [UNESP]; Schimming, B. C. [UNESP]; Santos, R. R. [UNESP]; Vulcano, L. C. [UNESP]; Linardi, J. L.; Teixeira, C. R. [UNESP] (Blackwell Verlag GmbH., 2015)
This study aimed to evaluate the stifle joint of marsh deer using imaging studies and in comparison with gross anatomy. Ten hindlimbs from 5 marsh deer (Blastocerus dichotomus) were used. Radiography, computed tomography (CT) and magnetic resonance imaging (MRI) were performed in each stifle joint. Two hindlimbs were dissected to describe stifle gross anatomy. The other limbs were sectioned in sagittal, dorsal or transverse planes. In the craniocaudal radiographic view, the lateral femoral condyle was broader than the medial femoral condyle. The femoral trochlea was asymmetrical. Subsequent multiplanar reconstruction revealed in the cranial view that the external surface of the patella was roughened, the medial trochlea ridge was larger than the lateral one, and the extensor fossa at the lateral condyle was next to the lateral ridge. The popliteal fossa was better visualized via the lateral view. Sagittal MRI images identified lateral and medial menisci, caudolateral and craniomedial bundles of cranial cruciate ligament, caudal cruciate ligament, patellar ligament and common extensor tendon. In conclusion, the marsh deer stifle presents some anatomical characteristics of the ovine stifle joint.